Evaluasi Infrastruktur Pejalan Kaki di Kawasan Lingkungan Perkotaan (Studi Kasus: Kawasan WR Supratman, Bandung) - Hamdani, Gildan Kantona (RUAS, 2024)
The uneven distribution of planning and provision of adequate pedestrian infrastructure stems from its focus on specific roads in certain areas. This research was conducted around Jalan W. R. Supratman, Bandung City, an urban environment where people live, with various facilities. We evaluate the pedestrian infrastructure using the criteria and aspects of PEQI, combining them with the applicable regulatory standards in Indonesia. PEQI serves as a quantitative observation tool that evaluates the quality and safety of the physical environment for pedestrians, taking into account the needs of the environment, segments, and intersections. The results of the evaluation show that the condition of pedestrian infrastructure in the area is inadequate. Improvements are needed to increase pedestrian interest in this area. The results of the evaluation can provide a basis for stakeholders to take planning steps to provide adequate pedestrian infrastructure in the city of Bandung.